The effects of iron deficiency anemia on sleep and life qualities - Sincan, Gulden; Sincan, Suat; Bayrak, Muharrem (Annals of Medical Research, 2022)
Aim: Iron deficiency anemia is an important public health problem all over the world. We aimed to determine the effects of anemia on sleep and life qualities in patients with iron deficiency anemia. Material and Methods: Ninety-nine iron deficiency anemia patients and fourty healthy cases were recruited. Short-Form 36-Item Health Survey questionnaire and Pittsburgh Sleep Quality Index questionnaire were used to measure the qualities of life and sleep, respectively. A Pittsburgh Sleep Quality Index global score >5 was defined as poor sleep quality. The gathered data were analyzed using descriptive, independent-t-test, chi-square tests. Results: The global Pittsburgh Sleep Quality Index score was 10.23±2.87 in patients with iron deficiency anemia and it was 3.65±1.4 in control group (p<0.001). The scores of each item for the Pittsburgh Sleep Quality Index were worse in patients with anemia than control group. The quality of life scores in the control group were higher compared with the anemia group (p<0.001). We also found a positive significant association between sleep quality and life quality in patients with anemia (p<0.001). Conclusion: We found that iron deficiency anemia negatively affects the qualities of sleep and life in adult patients. Therefore, we suggest that iron deficiency anemia should be investigated in the etiology of impaired sleep and quality of life.